Strategic Imperatives of Digital Convergence: Analysis of Transformative Dynamics, Organisational Recalibrations and Leadership Paradigms in the Context of Digitalisation - Norman SCHERER (Communications of International Proceedings, 2023)
Amidst the profound global impact of the SARS-CoV-2 virus, there emerges an accelerated shift towards digital transformation in various sectors, notably the real estate industry. This research addresses a notable gap in the academic literature regarding the interplay between digitalisation and leadership, specifically within the ambit of real estate. Leveraging a comprehensive analysis of primary and secondary sources, the study investigates the significant factors shaping digitalization’s influence on the economy and organisations, and how this interrelation affects leadership paradigms. The methodology entails a synthesis of extant concepts, with a focus on change management tools suited for the new digital era. Findings underscore the paramount importance of corporate culture and a well-communicated digital vision for successful transformation. Furthermore, leadership in the digital era requires a blend of traditional and novel competencies, emphasizing exemplary behaviour, trust-building, and adaptability. The study concludes that for businesses to thrive amidst digital upheaval, there must be a concerted effort to align organisational structures, leadership models, and employee engagement strategies with the digitalisation paradigm. This paper offers an in-depth analysis of the strategic imperatives generated by the converging forces of digital transformation. It focuses on the exploration of transformative dynamics, organisational recalibrations and novel leadership paradigms that are critical in a globally interconnected economic context. This paper critically analyses the challenges and opportunities for companies and presents innovative solutions to crises caused by pandemic and digital paradigm shifts. It covers aspects of corporate governance, organisational structure and employee motivation in detail and relates them to strategic and organisational levels as well as digital innovations. The aim of the article is to provide sound insights and recommendations for action based on a thorough literature review and the current economic situation.
Keywords: Digital Transformation; Organisational Recalibration; Leadership Paradigms; Corporate Governance